1986
DOI: 10.1139/v86-280
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoryl to carbonyl migration of amino groups in mixed anhydrides

Abstract: JILL SYMES and TOMA~Z A. MODRO. Can. J. Chem. 64, 1702(1986. Mixed anhydrides derived from carboxylic and amidophosphoric acids, (RO)(Rr2N)P(0)OC(O)R" (I), undergo unimolecular fragmentation yielding carboxyamides, R"C(0)NRf2, and metaphosphate esters, ROPO,. The mechanism of the amino group transfer was studied for substrate l a (1, R = R' = Me; R" = Ph); solvent as well as substituent effects indicate little (if any) charge development in the transition state. The effects of solvents and Lewis acids on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…An intriguing feature of path B is that it would constitute a new mechanistic pathway in which metaphosphate analogues could be formed. Usually metaphosphates and their analogues are generated from P(V) derivatives bearing a good leaving group and an internal nucleophile as is shown in Scheme . ,,,,, For cyclic phosphorus compounds, Z and X are part of a ring system, and fragmentation to metaphosphates occurs under pyrolytic conditions. , Other methods of metaphosphate generation, such as fragmentations of phosphoryl radicals, mixed phosphoric−carboxylic anhydrides or 2,4-bis(4-methoxyphenyl)-2,4-dithioxo-1,3,2,4-dithiadiphosphetane (Lawesson reagent), also have been developed; however, their applicability is limited to specific metaphosphate analogues.…”
Section: Resultsmentioning
confidence: 99%
“…An intriguing feature of path B is that it would constitute a new mechanistic pathway in which metaphosphate analogues could be formed. Usually metaphosphates and their analogues are generated from P(V) derivatives bearing a good leaving group and an internal nucleophile as is shown in Scheme . ,,,,, For cyclic phosphorus compounds, Z and X are part of a ring system, and fragmentation to metaphosphates occurs under pyrolytic conditions. , Other methods of metaphosphate generation, such as fragmentations of phosphoryl radicals, mixed phosphoric−carboxylic anhydrides or 2,4-bis(4-methoxyphenyl)-2,4-dithioxo-1,3,2,4-dithiadiphosphetane (Lawesson reagent), also have been developed; however, their applicability is limited to specific metaphosphate analogues.…”
Section: Resultsmentioning
confidence: 99%
“…Research flourished on several fronts during the existence of the Department of Organic Chemistry, the main areas being carbohydrate chemistry (Stephen, 1983(Stephen, , 1995(Stephen, , 2004Stephen et al, 1990); Cragg's steroid research and interest in borane chemistry (Cragg, 1975); Giles' synthetic group (Giles & Roos, 1976;Giles et al, 1979Giles et al, , 1984Giles et al, , 1994De Koning et al, 1991); Modro's active school of phosphorus chemistry (Modro, 1981;Hendrickse & Modro, 1984;Symes & Modro, 1986;Modro et al, 1987;Niven et al, 1988); Elsworth's work on the chemistry of marine organisms (Elsworth & Naude, 1986),and his participation in synthesis (Elsworth et al, 1988), and Campbell's burgeoning involvement in the chemistry and potential uses of fynbos constituents and medicinal plants (Campbell et al, 1980(Campbell et al, , 1986. The CSIR Fynbos Biome Research Unit was located on the top floor, otherwise occupied by the Department, and cooperation was maintained through its chemical director, a graduate of the Chemistry Department, Dr J.C. Patterson-Jones.…”
Section: Organic Chemistrymentioning
confidence: 99%
“…The same two groups of researchers introduced an ingenious method of trapping the intermediate metaphosphate species via the phosphorylation of the surface OH groups in silica gel [S]. Our own work showed that metaphosphate esters, RO-P02, can be extruded under mild conditions from 2-arylethylphosphorochloridates [6] or mixed amidophosphoric-carboxylic anhydrides [7]. In all the examples listed, the molecule of a precursor can be considered as a system in which the metaphosphate X-PO2 has been "inserted" into a more complex molecular framework and can be "released" from that framework through the bond-breaking and bond-making fragmentation processes.…”
Section: University Of Pretoriamentioning
confidence: 99%